The sociology of early Buddhism - Bailey, Greg, 1948- (Cambridge University Press, 2003)
Early Buddhism flourished because it took up the challenge represented by buoyant economic conditions in the newly emergent Indian states from the fifth century BCE. This book begins with the apparent inconsistency of Buddhism, a renunciant movement surviving within a strong urban environment, and draws out the implications of this.